Microstructure evolution, interface and mechanical properties of SiCp/2A14 joint during laser keyhole welding - Mingyang Zhang; Chunming Wang; Zhijia Hua; Yiyang Hu; Qiubao Ouyang; Gaoyang Mi (Journal of Materials Research and Technology, 2023)
Welding problems have restricted the applications of lightweight SiCp/Al composites in aerospace. In this work, the controllability of the keyhole mode, nucleation mechanism, and mechanical properties of the laser-welding process are studied in detail. The extrusion effect formed by the open keyhole pushes SiC particles to the bottom of the molten pool. To observe the nucleation and growth mechanism of the Al4C3 of keyhole laser-welded SiC/2A14Al composites, the dissolution–precipitation behavior of the SiC particles and growth behavior of the Al4C3 tip were observed. Owing to its high chemical properties, Al4C3 mainly begins nucleating from the open edges of the SiC particles and its formation is mainly distributed along the direction of Al grains. Al4C3 was the main crack source and propagation path while the small-sized SiC particles hindered the crack propagation. This work innovatively regulates the keyhole mode to achieve ‘small damage breakdown’ laser welding, greatly reducing the volume fraction of Al4C3. It also provides new insight into fusion welding of SiC particle-reinforced Al matrix composites.